The Iceman Cometh Across:: An Interview with Thomas Wharton - Wyile, Herb (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2002)
Author Thomas Wharton discusses the process of writing history in his historical novel Icefields (1995). He talks about the historical pioneering figures of the Canadian Rockies, the sense of "mountain metaphysics" he writes about, and the tradition of writing about the mountains. He also discusses the influence of modernism on his novel, calling Icefields "a modernist novel slightly out of its time." He comments on the relationship between Icefields and his second novel, Salamander.